Religious Moderation and Student Harmony: A Phenomenological Study of Duha Prayer Practices in Indonesian Overseas Schools - Rohayati, Sri; Hafni, Nur Laili Dina; Khoiri, Akhmad; Majid, Ikhwanuddin Abdul (Sekolah Tinggi Agam Islam Sumatera Medan, 2024)
Religious moderation needs to be instilled from an early age, not only through formal education, but also through daily practices. One example is the duha prayer in congregation, which as a sunnah practice requires tolerance from those of other religions. The practice is implemented in the Sanggar Bimbingan Gombak Utara in Malaysia, so this research aims to analyze the implementation with the focus of the study on efforts to build harmony, and the obstacles faced. This research uses a qualitative approach based on phenomenology, with data collected through interviews, observations, and documentation studies. Data analysis used the miles and huberman technique. The results reveal that the efforts made to build harmony include the implementation of an inclusive approach, integration of religious moderation in the curriculum, and parental involvement. The obstacles faced include a non-complex understanding of religious moderation and socio-cultural resistance. In the practice of duha prayer, students are accustomed to respecting differences in religious teachings, respecting time, and maintaining good friendships. The results of this study support Vygotsky's social constructivism theory, which emphasizes the role of social interaction in building shared understanding and values.